ANÁLISE DO CONSUMO ENERGÉTICO DE AMBIENTES COM USO DE COBOGÓS EM FOZ DO IGUAÇU - Camacho, Darwin Jaime; Sacht, Helenice María; Vettorazzi, Egon; Cardoso, Andréa Oliveira (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Foz de Iguazú is located in bioclimatic zone 3, where the climate is hot and humid, and for such, it is necessary the use of strategies and design solutions for improve the user's comfort architectural solution that can be used in this climate, since they provide natural ventilation and daylighting, as well as protection against solar radiation. Considering these aspects was evaluated the energy performance of an environment with use of cobogós (living room), comparing the results with a room with a simple glass window. For choosing the geometry of the cobogó, a mapping of the most sold cobogós was done in Foz do Iguaçu city, by means of the questionnaires application to the main stores of construction materials. The environment (living room) was proposed based on the building codes of the city using Revit software, and computer simulations were accomplished, using the Design Builder and Energy Plus programs. A comparative analysis was carried out, verifying that the use of cobogós presented an improvement in thermal comfort and energy efficiency, reducing the energy consumption